Numerical And Experimental Studies On Production Of Fine Silica In An Opposed Fluidized Bed Air Jet Mill - Munusamy, Sri Raj Rajeswari (2011)
This study is mainly focused on the production of fine silica in an opposed fluidized bed air jet mill through numerical and experimental techniques. In this mill, fine grinding occurs through collisions between solid particles in the continuous air stream. The stages in numerical techniques include the three-dimensional (3-D) modeling and simulations of the air jet mill using GAMBIT 2.3.16 and FLUENT 6.3 softwares. The major domain of the air jet mill and the nozzle parts consist of 144,237 elements of T-Grid mesh and 422 elements of Pave mesh respectively. The Eulerian Granular Model (EGM) approach with k-epsilon turbulence model and Syamlal-O’Brien drag function was adopted for modeling the air-solid flows in air jet mill. Validations of the CFD model with experimental and numerical results were made based on the mass output of silica from the jet mill. The mass difference within 11.50% to 19.97% indicates that the model is fairly suitable and satisfactory for simulations of fine grinding process. Variations in the operating variables of air jet mill influence the air-solid flow fields and the product characteristics. The air and solid velocities, and vary from 357.88 m/s to 509.86 m/s and 41.45 m/s to 57.82 m/s respectively, while the solid volume fractions, at the air jet mill’s pressure outlet are within 0.01 to 0.03.